PENGARUH CAPITAL INTENSITY, INVENTORY INTENSITY DAN SALES GROWTH TERHADAP TAX AVOIDANCE - Amri, Safana Aulia; Subadriyah, Subadriyah (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2023)
This research aims to measure and determine tax avoidance activities. This type of research uses a quantitative approach. The research population is all food and beverage industry companies (eight classes) listed on the Indonesia Stock Exchange for 2016-2020. The sample used in this study was 40 companies using a purposive sampling technique. The analytical tool used is multiple linear regression with SPSS tools. The study showed that capital intensity does not affect tax avoidance. Inventory intensity has a negative effect on tax avoidance. Meanwhile, sales growth has a positive effect on tax avoidance.